Improving higher education standards through reengineering in West African universities – A case study of Nigeria. Issue 8 (3rd August 2021) - Igwe, Paul Agu; Hack-Polay, Dieu; Mendy, John; Fuller, Ted; Lock, Deborah
ABSTRACT: This article examines the context of higher education (HE), policies and challenges in the West African context. A multi-level framework and analysis of reengineering, leading change in complexity, activity-based view of the University Business Model and Pedagogical Content Knowledge enable the development of deep connections between the macro- and meso-level and -micro challenges of Higher Education System (HES). These include elements of effective leadership, structures and curriculum and learning pedagogies. Drawing on the analyses of interviews from 25 overseas trained senior academics from Nigerian universities, a preliminary refinement of the philosophy of reengineering, re-thinking and revaluing the higher education system (HES) is offered. These have traditionally been addressed in a piecemeal perspective in HE policy and the academic literature; such a traditional approach has not been the systematic rethinking advocated in the philosophy of reengineering.